1994
DOI: 10.7556/jaoa.1994.94.8.647
|View full text |Cite
|
Sign up to set email alerts
|

Palpatory diagnosis and manipulative management of carpal tunnel syndrome

Abstract: Carpal tunnel syndrome was studied by use of supplemental palpatory diagnosis in 20 abnormal wrists. Restriction in motion at the carpal tunnel was quantified with a rating system. All wrists with carpal tunnel syndrome revealed at least moderate restriction to motion, as compared with only mild or no restriction in 20 wrists in normal, symptom-free subjects. Several participants (16 abnormal wrists) underwent osteopathic manipulative treatment, including a new "opponens roll" maneuver, and self-stretching, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 0 publications
5
28
0
4
Order By: Relevance
“…The performance of prehensile hand movement requires that the primary movers of the thumb (abductor pollicis brevis and opponens pollicis) are fixated at their base of attachment where they “anchor” to the transverse carpal ligament (TCL) [9, 10]. Fixation at the base allows muscle contraction to pull the thumb towards the other digits to generate maneuvers for controlled grasping.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The performance of prehensile hand movement requires that the primary movers of the thumb (abductor pollicis brevis and opponens pollicis) are fixated at their base of attachment where they “anchor” to the transverse carpal ligament (TCL) [9, 10]. Fixation at the base allows muscle contraction to pull the thumb towards the other digits to generate maneuvers for controlled grasping.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that fibrosis within the carpal canal of CTS patients prevents the MN from sliding out of harms way during routine hand activity. In fact, Sucher suggested that manipulation and stretching may be successful in alleviating symptoms of CTS by breaking up the adhesions or fibrous fixations [10]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies that used joint mobilization suggest moderate benefits in range of motion and a reduction of pain versus those who received no treatment (Akalin et al, 2002;Manente et al, 1999). Some evidence infers that manipulation and myofascial stretching may lengthen the flexor retinaculum, but these studies were performed on cadaveric tissue and extrapolation may be inappropriate (Sucher, 1994;Sucher and Hinrichs, 1998). Low-quality evidence supports the use of nerve-gliding 238 Cook and Goode/Physiotherapy Theory and Practice 23 (2007) 231À241 Physiother Theory Pract Downloaded from informahealthcare.com by Central Michigan University on 11/19/14 mobilization exercises (Akalin et al, 2002;Tal-Akabi and Rushton, 2000).…”
Section: Treatment Processmentioning
confidence: 94%